Role of different business models in scaling and adoption of Happy Seeder Technology in Haryana and Punjab - Vastrapur, Ahmedabad Gujarat (2017)
Every year the northern part of the India faces heightened air pollution during the month of November and December. The problem is such that one can easily feel the sensation in eyes and problem in breathing if one lives or travels to the region specially states like Punjab, Haryana, Delhi, Uttar Pradesh. Though the air pollution in this region can be a usual phenomenon round the year, the sudden heightened air quality deterioration has been attributed to the crop residue burning (CRB), by the farmers in these regions. CRB occurs when farmers after the harvest of the rice in the month of October or November, burn the straw which remains lying on the surface of the soil. There have been several reasons why the farmers are motivated to the practice of the burning the straw or say field in particular. The old age mindset of slash and burn with a perception that it is a good practice to burn the field which will keep the insects, diseases, weed seeds getting killed in the process. Non-availability of labor during the harvesting season to manage the residue. High silica content in rice straw which makes it unsuitable to be used as a feed for the livestock. Decline in number of cattle with the farmers which makes the straw useless for the farmers. Last but not least the most significant reason among the farmer to burn the straw is the Inability of farmers to manage the straw in a short duration between rice harvest and wheat sowing to catch up the right sowing time. The productivity of the wheat is very much dependent on the right time of sowing and to manage it. Many farmers rely on burning the straw in field which immediately frees land for tillage, leveling and seeding of rice in a well-prepared field. Moreover, the CRB is more viable to practice as the cost of in-situ (ex. incorporation in the field), and ex-situ (ex. Composting) management of the straw is high to the farmers making it economically unviable for the farmers to adopt. The combine harvester in cuts the crops with large stubble length and throws the straw in patches in large quantities. The straw and long length stubble makes the tillage operation difficult, costly, and a time taking operation. To get rid of the folly the farmers rely on CRB which makes them rid of the problem and further tillage can easily be done. CRB is normally followed by ploughing of soil twice using a disk plough, use of finger-like tyned implement called cultivator to break clods, planking to level the land and finally sowing of seeds using a fertilizer cum seed drill machine. So, speaking it takes five operations – ploughing twice using dick plough, use of cultivator, planking and sowing of seeds, in conventional method of wheat cultivation in the beginning of the crop. 6 CRB is not just detrimental to the air quality, but it also acts as a folly for the soil health. The residue which otherwise should have been incorporated in the soil to add soil organic carbon. Burning of soil leads to several problems such as soil erosion, organic matter loss, an imbalance in soil permeability and structure and loss of soil micro-organism and decline in long-term productivity (Hesammi et al., 2014).